2021
DOI: 10.1093/molehr/gaaa084
|View full text |Cite
|
Sign up to set email alerts
|

Metformin: a novel promising option for fertility preservation during cyclophosphamide-based chemotherapy

Abstract: Cyclophosphamide (CP) could cause severe gonadotoxicity via imbalanced activation of primordial follicles through PI3K/AKT/mTOR activation. Whether metformin, a widely prescribed anti-diabetes agent with mTOR inhibitory effect, could preserve ovarian function against CP toxicity is unknown. Female C57BL/6 mice were randomized into seven groups (n = 11), including control, CP-alone, CP + metformin, CP + sirolimus or everolimus, metformin-alone and sirolimus-alone groups. The duration of pharmaceutical treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 62 publications
1
0
0
Order By: Relevance
“…Serum AMH levels and the number of offspring were also higher in the group taking metformin [ 202 ]. A similar beneficial effect of metformin on reducing the ovotoxic effects of cyclophosphamide use was also confirmed in another study [ 203 ]. Also in a mouse model, Yang et al [ 204 ] showed that intragastric administration of metformin could alleviate ovarian damage and endocrine disruption caused by chemotherapeutic agents, with these effects being due to metformin’s reduction of oxidative stress and inflammation-related damage.…”
Section: Potential Ovarian-protective Mechanismssupporting
confidence: 72%
“…Serum AMH levels and the number of offspring were also higher in the group taking metformin [ 202 ]. A similar beneficial effect of metformin on reducing the ovotoxic effects of cyclophosphamide use was also confirmed in another study [ 203 ]. Also in a mouse model, Yang et al [ 204 ] showed that intragastric administration of metformin could alleviate ovarian damage and endocrine disruption caused by chemotherapeutic agents, with these effects being due to metformin’s reduction of oxidative stress and inflammation-related damage.…”
Section: Potential Ovarian-protective Mechanismssupporting
confidence: 72%